Abnormal cell proliferation in the p75NTR-positive basal cell compartment of the esophageal epithelium during squamous carcinogenesis. Issue 7 (1st October 2015) - Okumura, T.; Shimada, Y.; Sakurai, T.; Hori, R.; Nagata, T.; Sakai, Y.; Tsukada, K.
Summary: The low affinity neurotrophin receptor p75NTR is known to be expressed in the mitotically quiescent basal layer (BL) of the normal esophageal epithelium. The aim of the present study was to detect oncogenic changes in the p75NTR-positive BL during esophageal squamous carcinogenesis. The normal epithelium (NE), low-grade intraepithelial neoplasia (LGN), high-grade intraepithelial neoplasia (HGN), and esophageal squamous carcinoma (SCC), in which invasion was limited to the muscularis mucosa, were obtained from surgically removed esophagi. The expression of p75NTR, the proliferation marker ki67, hTERT, p53, and p63 was examined immunohistochemically. The expression of p75NTR was detected in these tissues with average staining indexes (number of stained cells/100 nucleated cells; SI) of 1.00, 0.99, 0.81, and 0.73, respectively. The expression of ki67 in the BL significantly increased with the progression from LGN to HGN. The expression of hTERT and p53 significantly increased with the progression from NE to LGN, and then increased in a stepwise manner in HGN and SCC, with SI (hTERT/p53) of 0.10/0.11, 0.32/0.45, 0.50/0.72, and 0.65/0.61, respectively. The expression of p63 showed no significant difference among NE, LGN, HGN, and SCC, with SI of 0.82, 0.77, 0.85, and 0.87, respectively. A correlation was observed between the expression of ki67 and p53 ( P = 0.005), while a negative correlation was found between p75NTR and hTERT ( P = 0.01). Our results demonstrated that phenotypic changes from quiescent to active proliferation in the p75NTR-positive BL occurred during the progression from LGN to HGN. The altered expression of hTERT and p53 in the BL was detected in LGN, which suggested that additional oncogenic events that disrupt mitotic regulation in the p75NTR-positive quiescent BL may play a crucial role in malignant transformation. Further investigations using the isolation and tracing of p75NTR-positive cells in precancerous epithelia may provide us with a better understanding of squamous carcinogenesis.